Hubungan Kualitas Pelayanan terhadap Kunjungan Ulang Pasien di Poliklinik Gigi dan Mulut Rumah Sakit Umum Puri Husadatama Kabupaten Mesuji - Alif Chandra Aryono; Atikah Adyas; Achmad Djamil; PA Kodrat Pramudho; Aila Karyus (Malahayati Nursing Journal, 2022)
ABSTRACT Quality health services will increase patient repeat visits. Puri Husadatama Hospital is the only private hospital in Mesuji Regency that provides dental and oral polyclinic services. The data of patients who visited the dental and oral polyclinic in 2020 were 194 people, and in 2021 there were 509 people. Fluctuations in inpatient visits and the Covid-19 pandemic have resulted in changes in service procedures that require patients and staff to carry out additional activities to implement health protocols. The purpose of the study was to determine the relationship between service quality and patient repeat visits to dental and oral services at the dental and oral polyclinic of Puri Husadatama Hospital in 2022. This type of research is an analytic survey with a cross-sectional approach. The population of 616 patients was those who visited the dental and oral polyclinic of Puri Husadatama Hospital from 2021 – February 2022. A sample of 110 people was taken by consecutive sampling. Data collection using a questionnaire in the google form. The analysis performed was univariate, bivariate using Chi-Square test. The results showed that the highest number of respondents were aged 26-45 years, (51.8%) and the female sex was 63.6%. While SMA education is 40.0%, not/not yet working is 47.3%. Patients with repeat visits 1 time amounted to 78.2%. Most quality dimensions were stated to be good from the tangible aspect (74.5%), Empathy (84.5%), reliability (96,4%) and responsiveness (93.6%), and assurance (97.3%). Chi-Square tests showed that the dimension variable of quality responsiveness had a significant relationship on repeat visits (p value=0.005).The dimension variable of quality responsiveness had a significant relationship on repeat visits. It is recommended to maintain an increase in patient repeat visits at the dental and oral polyclinic of Puri Husadatama Hospital, so that service officers and management continue to carry out the 5 dimensions of service quality, even during the Covid-19 pandemic.  Keywords: Service Quality, Dental, and Oral Polyclinic, Repeat Visits   ABSTRAK Pelayanan kesehatan yang berkualitas akan meningkatkan kunjungan ulang pasien. Rumah Sakit Puri Husadatama merupakan satu-satunya rumah sakit swasta yang ada di Kabupaten Mesuji yang memberikan pelayanan di poliklinik gigi dan mulut. Data pasien yang berkunjung ke poliklinik gigi dan mulut di tahun 2020 sebanyak 194 orang, dan tahun 2021 sebanyak 509 orang. Fluktiatifnya kunjungan pasien dan kondisi pandemi Covid-19 mengakibatkan perubahan prosedur pelayanan yang mengharuskan pasien dan petugas melakukan kegiatan tambahan penerapan protokol kesehatan. Tujuan penelitian untuk mengetahui hubungan kualitas pelayanan terhadap kunjungan ulang pasien pada pelayanan gigi dan mulut di poliklinik gigi dan mulut Rumah Sakit Puri Husadatama tahun 2022. Jenis penelitian adalah survei analitik dengan pendekatan cross sectional. Populasi sebesar 616 pasien adalah pasien yang berkujung ke poliklinik gigi dan mulut Rumah Sakit Puri Husadatama periode tahun 2021 – Febuari 2022. Sampel sebesar 110 orang diambil secara consecutive sampling. Pengumpulan data menggunakan kuesioner dalam google form. Analisis yang dilakukan adalah univariat, dan bivariat dengan uji Chi-Square. Hasil penelitian didapat jumlah terbanyak responden berumur 26-45 tahun, (51,8%) dan jenis kelamin perempuan 63,6%. Sedangkan pendidikan SMA 40,0%, tidak/belum bekerja 47,3%. Pasien dengan kunjungan ulang lebih dari 1 kali sebesar 78,2%. Dimensi kualitas pelayanan mayoritas dinyatakan baik dari aspek tangible (74,5%), Empathy (84,5%), reliability (96,4%) dan responsiveness (93,6%), serta assurance (97,3%). Uji Chi-Square menunjukkan variabel dimensi kualitas responsiveness berhubungan signifikan terhadap kunjungan ulang (p value 0,005). Variabel dimensi kualitas responsiveness berhubungan signifikan terhadap kunjungan ulang. Disarankan untuk menjaga peningkatan kunjungan ulang pasien di poliklinik gigi dan mulut Rumah Sakit Puri Husadatama, agar petugas pelayanan dan manajemen tetap melaksanakan 5 dimensi kualitas pelayanan, meskipun dalam masa pandemi Covid-19. Kata Kunci: Kualitas Pelayanan, Poliklinik Gigi dan Mulut, Kunjungan Ulang.